Critiquing the Postcolonial Nigeria in the Narratives of Ben Okri - Sharma, Khum Prasad (Prithvi Academic Journal, 2023)
The paper explores identity politics in the narratives of Ben Okri as they depict the Yoruba African myth. This study looks into the conditions of the culturally oppressed Africans in general and postcolonial Nigeria in particular that reframes the official version of colonial history. Myth offers reinterpretation and rethinking of the official colonial history in reclaiming the identity of the culturally excluded people with a variety of voices in response to the fictitious narrative. In line with this idea, I argue that the backdrop of postcolonial everyday life in Nigeria offers a chance to frame the topic of places more effectively. In order to comprehend and resolve the historical paradoxes and mysteries that are expressed in myth, magic and dreams, Thus, I analyze Okri’s book from the postcolonial perspective, considering sociopolitical and historical realities. In fact, Okri combines politics and the idea of history together, using his idea of an "inviolate" African consciousness as to show the foundation of how history dominates all other aspects. To justify my argument, this paper aims to examine how Okri reassesses history and encodes African consciousness in contrast to Western epistemology. Using African myths as a third eye in Okri’s novel, the paper also seeks to understand how Okri reimagines postcolonial potentials for his own Nigeria and, by extension, for the entire African continent.